Proposed upgrading to the existing interior design of Muny's Cafe and Bakery at Lot D-22-6A,D-22-6B, D-21-6A,D-21-6B, Jalan Prima Saujana 2/8, Seksyen 2, Taman Prima Saujana, 43000 Kajang for Muny's Sdn Bhd / Farah Adiba Karim - Karim, Farah Adiba (Faculty of Architecture, Planning and Surveying, 2012)
This is a project for upgrading Muny's Cafe & Bakery to make Muny's Cafe & Bakery as a centre for the students in Kajang. This is a good opportunity for Muny's to open a business in Kajang area because it is the students area and to expand its business in Kajang area. Muny’s Cafe & Bakery is located at Lot D-22-6A, D-22-6B, D-21-6A, D-21-6B Jalan Prima Saujana 2/B, Seksyen 2, Taman Prima Saujana, 43000 Kajang Selangor Darul Ehsan. The aim of this project is to create an environment where people can enjoy a joyful delight of freshly-baked bread and buns with affordable price. By using the style of cafe and bakery, upgrading Muny's in becoming a lifestyle cafe. Kajang area is a great site to expand the business. By using the research methods, this project have been identify the need and problems through questionaire, interview, internet and case studies around the proposed site. The issues of this proposed project is the circulation and traffic in existing space which complicates the workers. There is no space provided for the product to display to the customer and the current area also lacks space for a cafe extension and need a proper ventilations and airways. The design objective for this project is to create a space where the workers can work in condusive and comfortable area and proceeding for a good workflow to the working area, to provide a new space fto display their product and also to create a cafe space and proper design ventilation and airways.